Morality, Risk-Taking and Psychopathic Tendencies: An Empirical Study - Cacace, Sam; Simons-Rudolph, Joseph; Dubljević, Veljko (Frontiers in Psychology, 2022)
Research in empirical moral psychology has consistently found negative correlations between morality and both risk-taking, as well as psychopathic tendencies. However, prior research did not sufficiently explore intervening or moderating factors. Additionally, prior measures of moral preference (e.g., sacrificial dilemmas) have a pronounced lack of ecological validity. This study seeks to address these two gaps in the literature. First, this study used Preference for Precepts Implied in Moral Theories (PPIMT), which offers a novel, more nuanced and ecologically valid measure of moral judgment. Second, the current study examined if risk taking moderates the relationships between psychopathic tendencies and moral judgment. Results indicated that models which incorporated risk-taking as a moderator between psychopathic tendencies and moral judgment were a better fit to the data than those that incorporated psychopathic tendencies and risk-taking as exogenous variables, suggesting that the association between psychopathic tendencies and moral judgment is influenced by level of risk-taking. Therefore, future research investigating linkages between psychopathic tendencies and moral precepts may do well to incorporate risk-taking and risky behaviors to further strengthen the understanding of moral judgment in these individuals.